Do Minority-Serving Institutions Make a Difference in the Engagement and Outcomes of Minority College Students? Empirical Evidence from China - Yuheng Huang; Zengchen Han; Yu Tian; Yannan Cao (Behavioral Sciences)
This study uses nationally representative data from the Chinese College Student Survey (CCSS) (N = 37,508) to examine the impact of minority-serving institutions (MSIs) on learning opportunities, processes, and outcomes for ethnic minority college students. The CCSS uses a self-report questionnaire with multiple scales to measure ethnic minority students’ development, including family and ethnic background, university admission opportunities, learning behavior and psychology, and skill development in areas such as leadership and innovative thinking. We employ logistic regression and propensity score matching and find that MSIs offer valuable learning opportunities to minority students from ethnic areas and economically disadvantaged backgrounds, as well as those with weak academic preparation. Furthermore, these institutions enhance ethnic minority students’ engagement in active and cooperative learning, participation in high-impact educational activities, acquisition of knowledge and skills, innovative thinking, leadership development, and overall growth. However, MSIs are less effective at fostering interpersonal relationships. Additionally, MSIs exert a significant positive influence on college students from ethnic groups characterized by strong religious affiliations or low average educational levels, particularly in terms of learning behaviors and both academic and social integration.